Fasting Insulin and Risk of Cancer Related Mortality in Non-diabetic Adults: A Dose-response Meta-analysis of Cohort Studies - Ghanavati, Matin; Rahmani, Jamal; Rinaldi, Giulia; Zand, Hamid (Current Diabetes Reviews, 2020)
Background: Insulin is known to have direct and indirect effects on cell cycle progression, proliferation and metastatic activities. We performed a dose-response meta-analysis to investigate the association between hyperinsulinemia and all-cause cancer related mortality. Methods: A systematic literature search was conducted on MEDLINE and SCOPUS databases to include all published articles up to January 2019. Combined hazard ratios (HRs) with 95% Confidence Intervals (CIs) were estimated using DerSimonian and Laird random-effects models. A dose-response analysis was also conducted to further explore insulin’s relationship with cancer-related mortality. Results: We identified seven studies, with a total of 23,990 participants, who reported the association between hyperinsulinemia and cancer-related mortality. Results from the eligible studies indicated that higher fasting insulin levels were not associated with an increased risk of cancer mortality (pooled HR: 1.14, 95% CI: 0.99-1.32), however, significant heterogeneity was present (I2 = 60.3%, P heterogeneity = 0.001). A subgroup analysis based on gender demonstrated a significant association between fasting insulin level and cancer mortality in men (pooled HR: 1.92, 95% CI: 1.23-3.01, P heterogeneity = 0.281). Conclusion: This dose-response meta-analysis showed a direct significant association between fasting insulin level and cancer mortality in men.
Keywords: diabetes